The retreat from widening participation? The National Scholarship Programme and new access agreements in English higher education. Issue 2 (1st February 2016) - McCaig, Colin
Abstract : This article critically analyses the impact of reforms to the student financial support system in English higher education. Comparative analysis of financial support mechanisms and patterns of outreach engagement with groups underrepresented in higher education show a marked deterioration in the levels of cash support available and an increasingly focus on the brightest poor students (in the form of merit aid) at the expense of the generality of poorer students since the new support programme came into place. This can be seen as part of a wider policy shift away from generic widening participation to the targeting of specific cohorts to raise the attainment level of intakes or to meet recruitment shortfalls. The findings are located in a context of a (near) trebling of tuition fees, stagnation in overall student numbers and the promotion of market mechanisms, all of which can be seen as a challenge to the notion of social justice through the higher education system.